Caracterização de Plintossolos Argilúvicos na planície do rio Araguaia - Moura, Danillo Barbosa de (2015)
The Plain of Araguaia River is the largest in the Midwest Region of Brazil, sheltering a diversity of vegetal habitats, animals as well as soils, among which predominate Neosols, Gleisols and Plinthosols. These latter two reflect the water regime conditions of a high water table, being affected by redoximorphics processes. In the North of Goiás State there is a large irrigation project called “Luis Alves of Araguaia Project”, installed in 1997 in São Miguel do Araguaia, on top of Gleisols e Plinthosols subject to seasonal flooding for rice cultivation in full phase and soybeans in the ebb. However, there are almost no studies characterizing these soils, or the impacts of their use and management. The parent material is basically composed of clay-sand alluvial Holocene sediments. The climate is sub-humid tropical and the local vegetation is dominated by “varjões with Murundus”. The goal of this dissertation is to characterize two representative Argilluvics Plinthosols profiles, in two different positions of the landscape. The profiles were described and samples collected for physical, chemical, mineralogy and analysis micromorphology, and were classified according to the Brazilian System of Soil Classification (SiBCS) (Embrapa 2013). Both profiles are strongly acidic, with positive charge associated with a high amount of clay. In particular, in B horizons, Ca 2 + and Mg 2+ levels were found that were higher than those commonly found in the analyzed, as well as the presence of vermiculite layers of hydroxy (HIV). The plinthites were emphasized in the micromorphological, geochemical and mineralogical study in order to help in the interpretation of the pedogenetic process and stage of plinthization. An analysis of the results suggests that the presence of a concretionary horizon in depth profile on the edge of the plain, received micaschist contribution coming from the highest geomorphic surface outside the plain, confirming that the source material is not only flood, but has contribution relocated materials. The plinthites (nodules) are ferruginous and vary in depth according to their form, frequency, size and adhesion to the soil matrix, suggesting normal plinthization, that is, diffuse and large lumps halos at the base of the profiles, which evolve into diagnostic horizons where they become commonplace, thick, rounded, less adherent and more contrastive with the soil matrix and degrade towards the surface. These evidences prove that the plinthites are still forming in these soils in weather conditions to actually.